In the Era After the European Organisation for Research and Treatment of Cancer 'Boost' Study, is the Additional Radiotherapy to the Breast Tumour Bed Still Beneficial for Young Women?. Issue 6 (June 2020) - Beaton, L.; Chan, E.K.; Tyldesley, S.; Gondara, L.; Speers, C.; Nichol, A.
Abstract: Aims: The European Organisation for Research and Treatment of Cancer (EORTC) 22, 881–10, 882 trial showed significant benefit of a radiotherapy boost (RTB) in women ≤40 years in a pre-hormone therapy (HT) era. We determined how the use of HT and RTB changed in response to clinical guidelines and whether the benefit of routine RTB was still observed in the HT era. Materials and methods: Between 1996 and 2004, a provincial database identified all women ≤40 years with breast cancer who met the inclusion criteria of the EORTC trial. In total, 411 patients were classified into three eras defined by the guidelines: era 1 (discretionary HT, discretionary RTB); era 2 (routine HT, discretionary RTB); era 3 (routine HT, routine RTB). HT use, RTB use and cumulative incidence of local recurrence were calculated and compared across eras. Results: HT use increased after the first policy change from 13% to 75% for oestrogen receptor-positive patients ( P  < 0.01). RTB use also increased from 33% to 76% following the second policy change ( P  < 0.01). At 10 years, the cumulative incidence of local recurrence was 12% in era 1, 6% in era 2 and 6% in era 3 (era 2 versus era 3, P  = 0.92). For patients in the routine HT era (eras 2 and 3 combined) there was no significant difference in local recurrence between RTB and 'no RTB' patients (6% versus 7%, P  = 0.81). Conclusions: The routine use of HT and RTB increased significantly after new practice guidelines. Introduction of the HT guideline was associated with a 6% improvement in local recurrence at 10 years. No improvement in local recurrence was associated with the introduction of the RTB guideline in the HT era. The routine use of a boost in unselected young women with negative margins should be re-evaluated in the current HT era. Highlights: Prior to routine hormone therapy (HT) use, a boost (RTB) reduced breast cancer local recurrence in women ≤ 40 years. The use of HT and RTB increased significantly after the introduction of new practice guidelines. Local recurrence was halved after introduction of the HT guideline. No improvement in local recurrence was associated with the introduction of the RTB guideline in the HT era. The routine use of RTB in unselected young women with negative margins should be re-evaluated in the current HT era.